Design and Analysis of Venturi Microbubble Generator Using Computational Fluid Dynamics - Thoharudin, Thoharudin; Sunardi, Sunardi; Yudha, Fitroh Anugrah Kusuma; Nadjib, Muhammad; Nugroho, Arif Setyo (Eksergi, 2023)
The necessity for dissolved oxygen in water is crucial for the survival and growth of aquatic organisms, particularly tilapia. Seventy-five percent of tilapia will die if there is insufficient dissolved oxygen in the water. This work seeks to develop a venturi bubble-generating technique to combat the scarcity of dissolved oxygen in the water. A floating pump with a capacity of 12 m3/hour was selected as the medium for distributing water and generating vacuum pressure to draw in air for mixing with the water flow in the venturi. Ansys Fluent was used to model piping and venturi systems. The piping system was modeled with a single-phase (water) flow at a steady state, whereas the flow in the venturi was modeled with a multiphase (air and water) flow under transient situations. The simulation findings revealed that the pressure drop at the 90-degree elbow was much greater (27.17 kPa) than that at the 45-degree elbow (16.53 kPa). A 1-inch input diameter venturi produced bubbles with an average diameter of 105 µm, whereas a ½  inch venturi bubble generator produced bubbles with an average diameter of 83 µm. Owing to the numerous advantages of adopting a six-outlet piping system with a ½ inch venturi, this design is recommended for floating pumps with a capacity of 12 m3/h.